Fault detection, isolation and reconfiguration of a bipedal-legged robot. (October 2019) - Singh, Rajmeet; Bera, Tarun Kumar
This paper deals with the fault detection, isolation (FDI) and reconfiguration of the locomotion of a bipedal-legged robot. Initially, the planar model of the legged robot in the vertical plane is developed using a bond graph (BG) approach. Then, the planar BG model of the legged robot is extended to the three-dimensional legged robot. Two individual motors are used to actuate the prismatic leg of the robot for locomotion. The BG simulation provides results for straight walking based on an oscillating cylinder mechanism and the turning motion of the legged robot are discussed. The prototype model of the legged robot is also developed and experimentation is done for straight and inclined plane applications. Finally, an FDI technique for the three-dimensional model of a legged robot is developed for the generation of fault indicators (i.e., analytical redundancy relations; ARRs) in the presence of system failure. The ARRs are derived from the BG model of the legged robot during the occurrences of the fault. The experimental results are validated with the simulation results for FDI and reconfiguration when the robot manoeuvres in a U-shaped path. The real-time fault diagnosis and reconfiguration for locomotion of the legged robot is possible with this FDI approach.